2018
DOI: 10.1002/jcp.27187
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated microRNA‐27b attenuates lipopolysaccharide‐induced acute lung injury via activation of NF‐E2‐related factor 2 and inhibition of nuclear factor κB signaling pathway

Abstract: Acute lung injury (ALI) is a life-threatening, diffuse heterogeneous lung injury characterized by acute onset, pulmonary edema, and respiratory failure. Lipopolysaccharide (LPS) is a leading cause for ALI and when administered to a mouse it induces a lung phenotype exhibiting some of the clinical characteristics of human ALI.This study focused on investigating whether microRNA-27b (miR-27b) affects ALI in a mouse model established by LPS-induction and to further explore the underlying mechanism. After model es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 39 publications
(50 reference statements)
3
14
0
Order By: Relevance
“…in the present study, the expression of mir-27b was higher in the lPS-treated a549 group compared with that in the non-treated group. additionally, it was found that mir-27b overexpression reversed the protective effects of caSc2 expression on lPS-stimulated a549 cells, and the role of mir-27b in ali was consistent with the findings of a previous study (16).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…in the present study, the expression of mir-27b was higher in the lPS-treated a549 group compared with that in the non-treated group. additionally, it was found that mir-27b overexpression reversed the protective effects of caSc2 expression on lPS-stimulated a549 cells, and the role of mir-27b in ali was consistent with the findings of a previous study (16).…”
Section: Discussionsupporting
confidence: 90%
“…However, there are very few studies focused on the role of miR-27b in ALI. Huang et al (16) reported that mir-27b facilitated lPS-induced ali via nrf2 protein and the nF-κB signaling pathway. in the present study, the expression of mir-27b was higher in the lPS-treated a549 group compared with that in the non-treated group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated the involvement of miRNAs in the regulation of the inflammatory response in ALI. Several miRNAs, such as miR-24 and miR-27b, have been shown to attenuate lung injury in vitro and in vivo (45,46). miR-93 has previously been reported to play an important role in inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The PubMed database was searched between 1 January 2000 and 30 April 2019 under the following search strategy: (((antagomiR) OR (mirna antagonists) OR (mirna antagonist)) AND ((lung[MeSH Terms]) OR (“lung diseases”[MeSH Terms]))). In this analysis, we included original articles, published in English, whereas exclusion criteria included reviews, meta-analyses, single case reports, and studies published in a language other than English [3,7,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71].…”
Section: Methodsmentioning
confidence: 99%